The Role of the Malay Cultural Customary Council (MABM) in Preserving the Saprahan Tradition in Singkawang City - Alam, Fachrul; Sikwan, Agus; Astari, Zuri; Zatalini, Adhalia (International Journal Ethnic, Racial and Cultural Heritage, 2025)
This study explores the role of the Majelis Adat Budaya Melayu (MABM) of Singkawang City in preserving the Saprahan tradition, which constitutes an essential element of Malay Sambas cultural identity. MABM Singkawang, established as a traditional institution in 2007, is dedicated to safeguarding and revitalizing Malay customs, values, and cultural expressions in the midst of modernization and multicultural dynamics in Singkawang. The research employed a descriptive qualitative method, with data collected through in-depth interviews, participatory observation, and document analysis involving seven informants representing key cultural stakeholders. Data were analyzed through reduction, presentation, and conclusion drawing to provide a holistic understanding. Findings reveal that MABM carries out three major roles: providing understanding, supervising, and fostering preservation of Saprahan. The role of providing understanding is realized through educational seminars, cultural festivals, and community outreach programs that raise awareness about the values embedded in Saprahan, such as togetherness, mutual respect, and cooperation. The supervisory role is conducted through regular meetings, participation in community events, and direct monitoring to ensure that Saprahan remains aligned with its original cultural values. Meanwhile, fostering efforts are implemented through guidance programs in schools, cultural competitions like Besurong Saprah, and youth engagement activities aimed at transmitting cultural pride to younger generations. These strategies demonstrate MABM"™s commitment to ensuring the sustainability of Saprahan not only as a ritual of communal dining but also as a living tradition that strengthens social bonds, reinforces cultural identity, and contributes to the resilience of Malay heritage in Singkawang. This study highlights the importance of customary institutions as mediators of cultural continuity and provides insights into how traditional practices can be adapted and preserved in a rapidly changing social context.